Effectiveness of Gelatin Tannate among Children with Acute Diarrhea: A Systematic Review and Meta-Analysis - Farahdina Farahdina; Claudia Herda; Siti Habibah Zein; Vatine Adila (Budapest International Research and Critics University, 2021)
Gelatin tannate has been proposed as a theoretically effective treatment for treating acute diarrhea in children. Vegetable tannins have attracted a lot of attention in recent years because of their multifunctional properties, such as beneficial to human health and recently, an antidiarrhea effect of gelatin tannate has been reported. However, inconsistency across the studies was reported. This study aims to perform a meta-analysis concerning the efficacy of gelatin tannate administration for treating acute diarrhea in children Published papers from PubMed, Embase, Cochrane, and Google Scholar were collected, and they were analyzed using a fixed or random-effect model. A total of three relevant papers were included in our analysis. Our pooled analysis found that gelatin tannate administration, compared to control, was associated with reduced stool frequency (mean diff: 0.79 [95%CI: 0.44-1.15], p = 0.000). However, duration of diarrhea (mean diff: 10.87 [95%CI: -7.71-29.46], p = 0.25), weight gain (mean diff: 47.22 [95%CI: -22.81-117.24], p = 0.19), vomiting (OR: 0.57 [95%CI: 0.23-1.41], p = 0.22), and side effects (OR: 1.39 [0.42-4.63], p = 0.59) were not affected significantly between treatment and control groups. Gelatin tannate administration provides the efficacy to reduce stool frequency in children with acute diarrhea.